ANALISA ALTERNATIF TRASE DAN LALU LINTAS PEMBANGUNAN JEMBATAN TELUK SAWAIBU - Alfred Sanny Talaksoru; Atik Wahyuni (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
The main problem faced in West Papua Province is that there are still many road networks that have not been connected and several bridge points have not been built, therefore a special Acceleration of Development is needed in the field of Road Infrastructure and its supporters. The purpose of this research study was to find out the performance of the affected roads, namely JL Yos Sudarso and Jalan Merdeka, the need for lanes and the concept of movement after the construction of the Teluk Sawaibu bridge. The research method used is MKJI to calculate the volume and performance of the affected roads. Which is then used as a reference for determining the path and movement of vehicles. Based on the traffic analysis above, the alternative route chosen is the first route with a length of 300 meters, then for the road affected by Jalan Yos Sudarso to Jalan Merdeka with DS 0.56 then projected into traffic growth in 2021 over a 20-year building lifetime. obtained from the year 2021 to the 10th year (2031) the bridge requires 1 lane for 2 directions of movement, while for the 11th year onwards it requires 2 lanes for 2 directions of movement and for the concept of vehicle movement on the existing road both on the Yos Sudarso road as well as independent roads are made separate from the bridge, so that local residents can carry out normal activities without any interference from the movement of vehicles on the bridge.